Chromosomal breakage in normal and fragile X subjects using low folate culture conditions. - Vekemans, M (1983)
To investigate whether the fragile X syndrome is associated with a generalised chromosomal instability, we compared the frequency and distribution of chromosomal breakage in lymphocytes grown in low folate medium from normal subjects and from patients with the syndrome. Although low folate conditions increased the rate of chromosome breakage, no difference in frequency or distribution of chromosomal breakage was found between the two groups. This suggests that the fragile X syndrome is not associated with a generalised chromosome instability expressed in folate deficient medium and assessed in terms of chromosomal breakage.